Optimization of component in solution casted polylactic acid biocomposite by response surface methodology - M. A., Siti Nur E’zzati; Anuar, Hazleen; Y.F., Buys; A. R., Siti Munirah Salimah; Ali, Fathilah; M. R., Manshor (Springer Singapore, 2018)
The signifcant value of renewable resources used for food packaging has motivated consumer demand, thereby driving consumers to pay closer attention to biodegradable packaging applications. Polylactic acid (PLA) together with durian skin fbre (DSF), epoxidized palm oil (EPO) and cinnamon essential oil (CEO) have been used to produce thin flm via the solution casting method. This research study was conducted to optimise the potential efect of DSF content, EPO content and CEO content by determining the tensile properties of PLA biocomposites. The design of experiments (DOE) via response surface methodology was used to analyse the results. The optimum values for the tensile properties of PLA biocomposite were found at 3 wt% DSF, 5 wt% EPO and 1 wt% of CEO. The optimum tensile strength and tensile modulus of PLA composite were 24.9 and 375.9 MPa, respectively. The DSF content infuences the tensile properties of PLA biocomposite, followed by the EPO content and CEO content based on the analysis of variance. The P value of both responses in the design of experiments is less than 0.05 which verifes that the tensile properties model is signifcant. The coefcient, R2 , for tensile strength is 0.8908, while the coefcient result of the tensile modulus is 0.8916.